MODES OF DELIVERY IN SECOND PREGNANCY IN WOMEN WHO HAD ELECTIVE CAESAREAN SECTION FOR BREECH PRESENTATION IN FIRST PREGNANCY - Rabail Azeem,; Shabana Kokeb,; Kausar Inayat,; Nargis Danish ,; Talat Nelofer,; Sadaf Saifullah , (Journal of Ayub Medical College Abbottabad, 2024)
Background: The optimal management of breech presentation remains a debate among obstetricians worldwide. The Term Breech Trial (2000) highlighted elective caesarean section as a preferable method over vaginal delivery for breech presentations. This study investigates delivery modes in women who had an elective caesarean section for breech presentation in their first pregnancy. Objective was to evaluate delivery outcomes in the second pregnancy of women who had an elective caesarean section for breech presentation in their first pregnancy. Methods: A cross-sectional study was conducted at Jinnah International Hospital Abbottabad from October 10, 2018, to April 10, 2019. Data was collected from 321 women who had an elective caesarean section for breech presentation during their first pregnancy. The study used per-abdominal examination and obstetrical ultrasound to assess foetal presentation and recorded the mode of delivery in the second pregnancy. Results: Participants' ages ranged from 18 to 49 years, with a mean age of 28.87±4.07 years. The average interval between deliveries was 1.92±0.92 years, labour duration averaged 5.56±2.41 hours, and foetal head engagement averaged 2.92±1.35. Of the participants, 18.7% achieved a vaginal delivery, while 81.3% had a repeat caesarean section. Reasons for repeat caesarean included recurrent breech presentation in 44.9% and foetal distress in 32.4%. Conclusion: Approximately 18.7% of women who had an elective caesarean section for breech presentation in their first pregnancy achieved vaginal delivery in their second pregnancy, whereas the majority underwent another elective caesarean section.